The Revolutionary Impact on Customer Services After the Committee Recommendations on Indian Banking Sectors: Adapting to Change in the Banking Sector (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Thebanking sector is the lifeline of any modern economy .It is one of the vitalfinancial pillars of financial system, which plays an important role in thesuccess or failure of an economy. Banks are one of the oldest financialintermediaries in the financial system. They play an important role in themobilization of deposit and disbursement of credit to various sectors ofeconomy. The banking system is fuel injection systems which spurs economicefficiency of mobilizing savings and allocating them to high return investmentresearches confirm that countries wit well developed banking system grow fasterthen those with a weaker one. The banking system reflects the economic healthof a country. The strength of economy of a country basically hinges on thestrength and efficiency of the financial system which in the turn depends on asound and safe banking is prerequisite for the sustain growth of any economy.Banking system is the mirror of an economy playing a dominant role in thenational and global economy its contribution has a great contribution to GDPand is the most vibrant sector of the financial system. Banks in tandem withchange of pace in the financial sector are trying to become financialsupermarkets. Globalization, Liberalization & privatization have created amore competitive environment within the banking sector. The Indian bankingsector has witnessed a paradigm shift in its operation with initiation ofbanking sector reforms measure since 1991. The focus is gradually shifting frommass banking to class banking. The banking industry the world over hasundergone a profound transformation since early 1990s. The changed operatingenvironment for the banking sector, under pinned by globalization, deregulationand advances in information technology, has resulted in intense competitivepressures. Banks have responded to this challenge by diversifying throughorganic growth of existing business as well as through acquisitions. This hasexposed the banking sector to newer risks and posed serious regulatorychallenges. Regulatory and supervisory policies are, therefore beingcontinuously refined to meet the emerging challenges.